Effects of different intervention proposals in individuals with metabolic syndrome of Southern Brazil - Azambuja, Cati Reckelberg; Berté, Jéssica Karine; dos Santos, Daniela Lopes (Seven Editora, 2023)
Background: Metabolic Syndrome (MetS) has increased in all ethnicities and age groups of the world population. Understanding the effects of different exercise programs on MetS risk factors is necessary for the control of the syndrome. Objective: The objective of this study was to analyze the effects of different intervention proposals on individuals with MetS. Methods: Participants were 69 adults, of both sexes, with a mean age of 52.44±2.22 years and a medical diagnosis of MetS, from a city in southern Brazil. Five physical training proposals were tested: Combined Training without Nutritional Monitoring; Combined Training with Nutritional Monitoring; Strenght Training; Aerobic Interval Training; Functional Training. Individuals were evaluated before and after interventions in anthropometric, hemodynamic, functional and biochemical aspects. Results: The methods with thegreatest number of effects were Aerobic Interval Training, followed by Combined Training with Nutritional Monitoring. The waist circumference variable reduced only in the Aerobic Interval Training method (p